1994
DOI: 10.1007/bf01776489
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory conditioning by self-stimulation in rats: A pilot study

Abstract: This article describes an experimental attempt to condition breathing pattern in rats. In this experiment, a freely moving rat was first rewarded by an electrical stimulation of the medial forebrain bundle whenever inspiratory duration (TI) exceeded 300 ms. A bidirectional control was then used: TIs longer than 400 ms were rewarded, and then TIs shorter than 300 ms were rewarded. The frequency of TIs longer than 300 ms increased when this event was rewarded, further increased when TIs above 400 ms were rewarde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A review by Ley concluded that “breathing behavior is amenable to the principles of Pavlovian and operant conditioning” (Ley, 1999). Operant conditioning protocols have had some success altering respiration in rats and humans (Gallego et al, 1994; Ley, 1999; Elliott and Izzo, 2006). Our laboratory recently devised a yoked-control operant paradigm to investigate slow breathing as a technique to reduce stress reactivity (Noble et al, 2017a).…”
Section: Future Directions and Proposed Studiesmentioning
confidence: 99%
“…A review by Ley concluded that “breathing behavior is amenable to the principles of Pavlovian and operant conditioning” (Ley, 1999). Operant conditioning protocols have had some success altering respiration in rats and humans (Gallego et al, 1994; Ley, 1999; Elliott and Izzo, 2006). Our laboratory recently devised a yoked-control operant paradigm to investigate slow breathing as a technique to reduce stress reactivity (Noble et al, 2017a).…”
Section: Future Directions and Proposed Studiesmentioning
confidence: 99%
“…Programs of remedial breathing (often referred to as breathing retraining) provide obvious examples of clinical applications of operant conditioning in correcting dysfunctional breathing (see Timmons, 1994), and programs of research on operant control of breathing in the laboratory are gaining attention (e.g., Gallego et al, 1986;Gallego & Camus, 1989;Gallego & Perruchet, 1991a, 1991b. Preliminary evidence that inspiration duration, as a conditioned operant, can be modified in the rat by means of reinforcement consisting of electrical stimulation of the medial forebrain bundle can be found in a study by Gallego et al (1994). Although this single-case study limits generalizations, the unique method for the measurement of ventilation employed provides an exemplary model for future research in this promising but relatively unexplored region of respiratory psychophysiology.…”
Section: Operant Control Of Breathingmentioning
confidence: 99%
“…Classical conditioning approaches remove the volitional component involved in human SRR techniques, produce a range of respiratory responses that are not limited to changes in RR, and strongly depend on the unconditioned stimulus used to initially provoke the response (Gallego and Perruchet, 1991 ; van den Bergh et al, 1995 ; Nsegbe et al, 1997 , 1998 ). In comparison, operant conditioning protocols have had limited success altering respiration in rats and humans (Gallego et al, 1994 ; Ley, 1999 ; Elliott and Izzo, 2006 ). The only successful attempt to (indirectly) operantly condition RR in the rat was a pilot study that used electrical stimulation of the medial forebrain bundle as reinforcement (Gallego et al, 1994 )—and this study only included one animal.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, operant conditioning protocols have had limited success altering respiration in rats and humans (Gallego et al, 1994 ; Ley, 1999 ; Elliott and Izzo, 2006 ). The only successful attempt to (indirectly) operantly condition RR in the rat was a pilot study that used electrical stimulation of the medial forebrain bundle as reinforcement (Gallego et al, 1994 )—and this study only included one animal.…”
Section: Introductionmentioning
confidence: 99%